The Impact Of Drug Interactions On The Effectiveness Of Prescribed Treatments In Elderly Patients (The Review of Diabetic Studies, 2025)
Background: The increasing number of elderly individuals has led to a higher prevalence of chronic illnesses, necessitating the use of multiple medications. Polypharmacy raises the risk of drug interactions, potentially compromising the effectiveness of treatments and increasing the likelihood of adverse drug reactions. This study aims to assess the prevalence, severity, and associated factors of drug interactions in elderly patients and their impact on treatment outcomes.Methods: A cross-sectional study was conducted in 2024, including 300 elderly patients (≥60 years) receiving treatment for chronic conditions. Data collection involved structured interviews and electronic medical record reviews. Potential drug interactions were identified using IBM Micromedex DrugReax software and categorized as contraindicated, major, or moderate. Statistical analyses were performed to determine associations between drug interactions and clinical variables, including polypharmacy, comorbidities, and medication regimen complexity.Results: Drug interactions were highly prevalent, with 86% of participants experiencing at least one interaction. Major interactions, which could be life-threatening or require urgent medical intervention, were observed in 42% of cases. The most frequently implicated drug classes included angiotensin-converting enzyme inhibitors, diuretics, beta-blockers, anticoagulants, and antidiabetics. Significant risk factors for drug interactions included older age (≥70 years), female gender, polypharmacy (≥5 medications), high medication regimen complexity (MRCI >16.5), and multiple comorbidities, particularly diabetes mellitus, chronic kidney disease, and hypothyroidism (P